Australia's Experience of Combining Building Energy Standards and Disclosure Regulation - Berry, Stephen; Moore, Trivess; Ambrose, Michael (Frontiers in Sustainable Cities, 2022)
Multiple market failures have historically delivered housing that is environmentally and economically sub-optimal. Minimum energy standards are a popular policy tool for lowering energy use and anthropogenic carbon emissions in the built environment, but evidence shows they fail to drive performance beyond that minimum. Mandating the disclosure of energy performance on sale or lease of property has been introduced in some jurisdictions to transform the building stock and encourage energy and carbon saving improvements. These policy instruments address different market failures and have the potential to act as complementary regulation, but to date there has been little evidence that the combination may deliver greater benefits than each individual policy measure. The analysis of 342,674 housing energy assessments in Australia from May 2016 – June 2021 highlights the impact of complementary versus single policy instruments. We find that the building regulatory process alone delivers certainty regarding minimum performance, but when matched with disclosure regulation, the market is pulled slightly towards higher performance outcomes than for where building regulations alone are used. While only a small improvement in performance, the data supports the power of complementary regulation for long-life housing assets, similar to the benefits found for shorter-life assets such as household appliances; in essence creating both a carrot and a stick for consumers and the wider market. The data from Australia presented in this paper suggests that the use of complementary regulation may deliver improved environmental and economic outcomes and could help jurisdictions governing a transition to more sustainable housing as part of the wider transition to sustainable cities.